Արդիականացման չինական մոդելը տնտեսական և քաղաքական զարգացման համատեքստում - Լ. Զ. Նուրբեկյան (ՀՀ ԳԱԱ հրատ.)
Важной задачей современной политологии является анализ и обобщение политических и экономических процессов, происходящих в мире. В силу сказанного весьма интересен пример КНР, добившейся огромных успехов в проведении социально-экономических преобразований. The important task of modern political science is the analysis and synthesis of political and economic processes which take place in the world. Of particular interest is China that has achieved major success in carrying out social and economic reforms.
Keywords: Political Science; Modern History; Economic Theory; History; D History; H Social Sciences; J Political Science